Fine‐needle aspiration cytology of epithelioid malignant peripheral nerve sheath tumor: A case report and review of the literature. Issue 3 (9th December 2015) - Jiwani, Shahanawaz; Gokden, Murat; Lindberg, Matthew; Ali, Sumera; Jeffus, Susanne
Abstract : The epithelioid variant of malignant peripheral nerve sheath tumor (eMPNST) is an extremely rare soft tissue neoplasm comprising less than 5% of all MPNSTs. It is distinguished cytomorphologically from a conventional MPNST by the presence of polymorphous round epithelioid cells arranged in loose clusters with or without spindled tumor cells. These features pose a diagnostic challenge because the differential diagnosis involves a variety of mesenchymal and non‐mesenchymal tumors including epithelioid sarcoma, sclerosing epithelioid fibrosarcoma, malignant rhabdoid tumor, chordoma, metastatic carcinomas, and melanoma. Thus, it may become imperative to perform immunochemical stains on cell blocks of FNA aspirates to arrive at definitive diagnosis. Reports describing the cytologic features of eMPNST are rare. Herein, we report a case of eMPNST with focus on cytomorphologic and cytoimmunochemical features and differential diagnosis. Diagn. Cytopathol. 2016;44:226–231. © 2015 Wiley Periodicals, Inc.